2020
DOI: 10.3390/biomedicines8120544
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment with a Phytosomal Preparation Containing Centella asiatica L. and Curcuma longa L. Affects Local Protein Synthesis by Modulating the BDNF-mTOR-S6 Pathway

Abstract: Brain derived neurotrophic factor (Bdnf) is the most diffuse neurotrophin in the central nervous system and it is crucial for the proper brain development and maintenance. Indeed, through the binding to its high affinity receptor TRKB and the activation of different intracellular cascades, it boosts cell survival, neurite growth and spine maturations mechanisms. Here, we evaluated if the chronic oral treatment for 10 days with a phytosomal preparation containing Centella asiatica L. and Curcuma longa L. could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…However, deregulation of this protein has been shown to be associated with tumorigenicity and cancer cell progression in mouse xenotransplantation model [ 38 ]. Overexpression of EEF2 correlates with cancer cell growth, metastasis invasion, and poor prognosis in acute myeloid leukemia, breast, and lung cancer [ 39 41 ]. Report indicated that significantly higher incidence of tumor recurrence and worse prognosis were found in elevated EEF2 patients, whereas silencing of eEF2 expression increased mitochondrial elongation and cellular autophagy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, deregulation of this protein has been shown to be associated with tumorigenicity and cancer cell progression in mouse xenotransplantation model [ 38 ]. Overexpression of EEF2 correlates with cancer cell growth, metastasis invasion, and poor prognosis in acute myeloid leukemia, breast, and lung cancer [ 39 41 ]. Report indicated that significantly higher incidence of tumor recurrence and worse prognosis were found in elevated EEF2 patients, whereas silencing of eEF2 expression increased mitochondrial elongation and cellular autophagy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…[97][98][99] The non-ionic surfactants create a stable bilayer vesicle in hydrophilic systems by using energy (physical agitation and heating). 100,101 Hydrophobic parts in the bilayer structure are guided aside from the aqueous phase, while the hydrophilic heads stay in contact with the aqueous side. The surfactants used in the preparation of niosomes should be biocompatible, biodegradable, and not immunogenic.…”
Section: The Niosomementioning
confidence: 99%
“…Our findings supported the use of this preparation in subjects with memory and cognitive impairment. 101 The Phytosomes in Neurodegenerative Diseases 6996 investigated the nanoparticle system to improve the drug delivery or active compounds with poor availability to the brain. 183 Langasco et al studied the brain delivery of the isoflavone genistein testing various nanotechnological approaches; oxidative stress in PC12 cells (neuron cell line) was diminished by treatment with phytosomes, and the effect was better than the unformulated genistein.…”
Section: Evidence On the Role Of Phytosomes In The Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Sbrini et al investigated the effect of the chronic oral treatment for 10 days with a phytosomal preparation containing Centellaasiatica and Curcumalonga on brain-derived neurotrophic factor (BDNF) levels in prefrontal cortex of adult rats. The phytosome ameliorates brain plasticity, enhancing mTOR-S6 regulated transcription of proteins involved in memory processes, suggesting that this preparation can be used as a supporting therapy in subjects with memory and cognitive disfunction [ 16 ]. Behl et al discussed withaferin A (WA) pharmacokinetics, synergistic combination, and biological activities.…”
mentioning
confidence: 99%